2003
DOI: 10.1046/j.1095-8649.2003.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiration of steelhead trout sperm: sensitivity to pH and carbon dioxide

Abstract: Steelhead trout Oncorhynchus mykiss sperm held in seminal plasma or sperm‐immobilizing buffer (pH 8·6) at 10° C consumed O2 at the rate of c. 2 nmol O2 min−1 10−9 sperm; the rate of O2 consumption was not different in sperm held for 4 or 24 h. Decreasing the extracellular pH from 8·5 to 7·5 either by diluting semen with buffer titrated with HCl or by increasing the partial pressure of CO2 in the incubation atmosphere resulted in c. a 40% decrease in the rate of sperm respiration. The data did not, however, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…The inhibition of motility of sperm in semen is mainly due to osmotic pressure in most species (Morisawa and Suzuki 1980, Stoss 1983, Linhart et al 1991, Billard et al 1995a) but K þ plays a major role in salmonids (Schlenk and Kahmman 1938, Stoss 1983, Billard et al 1995b) and in sturgeons (Gallis et al 1991, Billard 2000. Several parameters of the swimming medium, such as ion concentration (K þ , Na þ , Ca 2þ , Mg 2þ ), osmotic level, pH and dilution rate, affect the motility duration of fish spermatozoa (Morisawa and Suzuki 1980, Stoss 1983, Linhart et al 1991, Billard et al 1995b, Tvedt et al 2001, Ingermann et al 2003. Optimum sperm motility was observed in alkaline pH and with a low dilution rate (at 1:50) in Acipenseridae (Gallis et al 1991, Alavi et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of motility of sperm in semen is mainly due to osmotic pressure in most species (Morisawa and Suzuki 1980, Stoss 1983, Linhart et al 1991, Billard et al 1995a) but K þ plays a major role in salmonids (Schlenk and Kahmman 1938, Stoss 1983, Billard et al 1995b) and in sturgeons (Gallis et al 1991, Billard 2000. Several parameters of the swimming medium, such as ion concentration (K þ , Na þ , Ca 2þ , Mg 2þ ), osmotic level, pH and dilution rate, affect the motility duration of fish spermatozoa (Morisawa and Suzuki 1980, Stoss 1983, Linhart et al 1991, Billard et al 1995b, Tvedt et al 2001, Ingermann et al 2003. Optimum sperm motility was observed in alkaline pH and with a low dilution rate (at 1:50) in Acipenseridae (Gallis et al 1991, Alavi et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…External pH in a wide range does not influence freshwater fish sperm motility (Alavi and Cosson, 2005). On the other hand, acidification of extracellular environments suppresses sperm motility in white sturgeon and trout (Ingermann et al, 2002(Ingermann et al, , 2003Alavi and Cosson, 2005). It is possible that sperm motility initiation regulation in A. burtoni accommodates different ionic environments of lake and river water with respect to Na 1 and K 1 , but not H 1 .…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the rivers that flow into the lake are acidic (pH 6.5). It has been reported that pH impacts have little effect on sperm motility activation (Ingermann et al, 2002(Ingermann et al, , 2003Alavi and Cosson, 2005). Among Tanganyikan cichlids, A. burtoni can inhabit and reproduce in both the lake and rivers.…”
mentioning
confidence: 97%
“…glycine, glucose or lactate plus pyruvate) the lactate plus pyruvate seems to be the most favourable to maintain ATP concentration. ATP level in spermatozoa of different species have been positively correlated with good motility (Ingermann et al 2003). It means that good ATP level is strictly related to good motility and finally to better fertilising potential.…”
Section: Discussionmentioning
confidence: 98%